Volume 1: Turbomachinery 1991
DOI: 10.1115/91-gt-007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Swirling Flow in the Internal Volute of a Centrifugal Compressor

Abstract: A detailed study of the swirling flow in a rectangular volute of a centrifugal compressor is presented. The 3D flow field has been measured by means of a five hole probe at six different cross sections for three different operating points of the compressor. For high mass flow, the large radial velocity component at the diffuser exit creates a strong swirling flow with a forced vortex type of velocity distribution. The centrifugal force resulting from this motion is balanced by the increase of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Related studies have found that the secondary flow in the volute plays the major role on the pressure distortion and velocity distribution in the volute, furthermore, the three-dimensional flow field characteristic in the volute should be also considered [6][7][8] . Gu, et al [9] investigated the interference between the volute and the impeller under off-design condition with numerical method.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have found that the secondary flow in the volute plays the major role on the pressure distortion and velocity distribution in the volute, furthermore, the three-dimensional flow field characteristic in the volute should be also considered [6][7][8] . Gu, et al [9] investigated the interference between the volute and the impeller under off-design condition with numerical method.…”
Section: Introductionmentioning
confidence: 99%
“…The highly three dimensional flow field inside the centrifugal compressor and pump volutes has been measured by Peck(1951), Muller(1973), Van den Braembussche and Hande(1990), Elholm et al(1990), Ayder and Van den Braembussche(1991).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed measurements by Ayder et al indicated a very complex, threedimensional (3D) flow within the volute and gave fundamental insights for further research [2][3][4]. It is well known that the volute flow causes a rotationally non-symmetric pressure distribution in the diffuser outlet at off-design conditions: the volute acts as a diffuser at lower than design mass flow and as a nozzle at higher than design mass flow, respectively.…”
Section: Introductionmentioning
confidence: 99%